Nuremberg Trials (Harvard Law School Library's Nuremberg Trials Project)
The Harvard Law School Library's Nuremberg Trials Project is an open-access initiative to create and present digitized images and full-text versions of the Library's Nuremberg Trials documents, descriptions of each document, and general information about the trials. The project provides access to the documentary record and other associated materials for all thirteen trials. We currently offer page images and searchable document descriptions for all documents as well as searchable full-text versions for most prosecution exhibits and most of the trial transcripts. Both prosecution and trial exhibits as well as all trial transcripts are currently only offered in the English-language versions used at the time of the Trials. Important: when citing from documents and transcripts, always verify the exact wording by consulting the accompanying page images of the document in question. The full-text versions of transcripts and documents are a product of human- and computer-aided transcription and may deviate in small ways from the originals.
Keywords: _open access

American Prison Newspapers, 1800s-present: Voices from the Inside - JStor
Overview On March 24, 1800, Forlorn Hope was published within a prison in New York state, edited by an incarcerated person. In the intervening 200+ years, over 700 prison newspapers have been published from U.S. prisons in all fifty states. American Prison Newspapers will bring together hundreds of these periodicals from across the country into one collection that will represent penal institutions of all kinds, with special attention paid to women-only institutions. With the United States in...
Keywords: _open access